Chloroplast engineering and RNA interference: A dual-technology approach for insect pest control - Akbar, Babur Ali; Arshad, Muhammad Awais; Khalid, Burhan; Baloch, Rania; Ahmad, Ali; Rouf, Sana; Ashraf, Muhammad Atiq; Mushtaq, Muhammad Zeeshan; Riaz, Talha; Maqbool, Rizwan (Journal of Pure and Applied Agriculture, 2025)
The integration of chloroplast engineering and RNA interference (RNAi) technologies represents a groundbreaking approach for sustainable insect pest management in agriculture. This review highlights the combined potential of these technologies to address the escalating challenges posed by insect pests, particularly in the context of increasing resistance to conventional insecticides. Chloroplast engineering provides a robust platform for the high-level expression of double-stranded RNA (dsRNA), essential for effective RNAi-mediated gene silencing in pests. The unique features of chloroplasts, such as their high copy number, transgene stability, and maternal inheritance, significantly reduce the risk of gene flow and non-target effects, making them an ideal system for dsRNA production. Recent advancements in transplastomic plants have demonstrated the efficacy of this approach in controlling economically significant pests, including aphids, whiteflies, and cotton bollworms. The review discusses the mechanisms underlying plant-mediated RNAi and explores innovative dsRNA delivery methods, such as nanoparticle-based systems, which have the potential to enhance RNAi efficacy. Additionally, the review addresses the environmental and biosafety considerations of RNAi-based pest control, emphasizing the need for eco-friendly alternatives to chemical pesticides. By leveraging the strengths of chloroplast engineering and RNAi, this integrated approach not only provides a sustainable and effective strategy for pest management but also paves the way for future innovations in crop protection and agricultural sustainability. This review underscores the importance of continued research and development in this field to address the growing challenges of global food security and environmental protection. The integration of these technologies offers a promising solution to reduce the reliance on chemical pesticides, mitigate the impact of insect pests on crop yields, and promote a more sustainable agricultural future.